2022
DOI: 10.3390/nu14030442
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Cancer Prognosis, Malnutrition Risk, and Quality of Life: A Cross-Sectional Study

Abstract: The present cross-sectional prospective study (from January 2017 until December 2020) aimed to evaluate the interrelation between nutritional parameters at the initial evaluation with the changes in QOL indicators and the Progression-Free Survival and Overall Survival in 97 patients with pancreatic cancer. Dietary and nutritional risk assessments, and an evaluation of Frailty and Functional Status were performed. Health-related Quality of Life was evaluated with the EORTC QLQ-C30 questionnaire. Nutritional ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…However, we did not observe a significant effect on non-infectious complications, POPF, DGE, SIRS duration, mortality, or immune and inflammatory markers such as IL-6 and CRP. Pancreatic cancer patients commonly experience nutritional abnormalities and cachexia, with up to 85% reporting malnutrition and nearly 71% of those with pancreatic and periampullary cancers experiencing cachexia, which is associated with a higher mortality rate [24,25]. Thus, the nutritional status of patients undergoing pancreaticoduodenectomy should be closely monitored.…”
Section: Discussionmentioning
confidence: 99%
“…However, we did not observe a significant effect on non-infectious complications, POPF, DGE, SIRS duration, mortality, or immune and inflammatory markers such as IL-6 and CRP. Pancreatic cancer patients commonly experience nutritional abnormalities and cachexia, with up to 85% reporting malnutrition and nearly 71% of those with pancreatic and periampullary cancers experiencing cachexia, which is associated with a higher mortality rate [24,25]. Thus, the nutritional status of patients undergoing pancreaticoduodenectomy should be closely monitored.…”
Section: Discussionmentioning
confidence: 99%
“…A prospective study of 97 patients with pancreatic cancer by Poulia et al. ( 20 ) showed that impaired preoperative nutritional status was associated with shorter RFS and OS. Therefore, the preoperative evaluation of the nutritional and immune status of patients with BRPC is very important for the choice of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of the subject to digest, absorb and metabolize food is compromised and then weight loss can be severe. In patients with head and neck cancer [35], instead, weight loss was explained as a side effect of cancer treatment; chemo and radiation therapies, or even surgery, can damage the mouth parts or the rst sections of the digestive tract, making it hard chewing, swallowing, compromising the salivary secretion and the digestive enzyme activity. These patients were in fact the majority of those who reported symptoms such as dry mixing bowl, loss of taste and smell, and decreased salivary secretion.…”
Section: Discussionmentioning
confidence: 99%